(untitled) (المجلة الدولية للبحوث العلمية, 2024)
The primary objective of this report is to use the Osterwalder and Pigneur (2010) Business Model and apply on the brief descriptions of the given three companies, i.e. an online accountancy service provider Alaw, a daily blog for travel and products called Bodnant Blogs and a cake bakery called Caradog Cakes. The report consists of three sections for each of the three companies. Each section presents the business model for the respective company initially, followed by a discussion on each of the nine blocks of the business model.